Exchange rates behaviour in Ghana and Nigeria: is there a misalignment? - Mapenda, Rufaro (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2011)
Exchange rates are believed to be one of the major driving forces behind sustainable macroeconomic growth and it is therefore important to ensure that they are at an appropriate level. Exchange rate misalignment is a situation where the actual exchange rate differs significantly from its equilibrium value, resulting in either an overvalued or an undervalued currency. The problem with an undervalued currency is that it will increase the domestic price of tradable goods whereas an overvalued currency will cause a fall in the domestic prices of the tradable goods. Persistent exchange rate misalignment is thus expected to result in severe macroeconomic instability. The aim of this study is to estimate the equilibrium real exchange rate for both Ghana and Nigeria. After so doing, the equilibrium real exchange rate is compared to the actual real exchange rate, in order to assess the extent of real exchange rate misalignment in both countries, if any such exists. In order test the applicability of the equilibrium exchange rate models, the study draws from the simple monetary model as well as the Edwards (1989) and Montiel (1999) models. These models postulate that the variables which determine the real exchange rate are the terms of trade, trade restrictions, domestic interest rates, foreign aid inflow, income, money supply, world inflation, government consumption expenditure, world interest rates, capital controls and technological progress. Due to data limitations in Ghana and in Nigeria, not all the variables are utilised in the study. The study uses the Johansen (1995) model as well as the Vector Error Correction Model (VECM) to estimate the long- and the short-run relationships between the above-mentioned determinants and the real exchange rate. Thereafter the study employs the Hodrick-Prescott filter to estimate the permanent equilibrium exchange rate. The study estimates a real exchange rate model each for Ghana and Nigeria. Both the exchange rate models for Ghana and Nigeria provide evidence of exchange rate misalignment. The model for Ghana shows that from the first quarter of 1980 to the last quarter of 1983 the real exchange rate was overvalued; thereafter the exchange rate moved close to its equilibrium value and was generally undervalued with few and short-lived episodes of overvaluation. In regard to real exchange rate misalignment in Nigeria prior to the Structural Adjustment Program in 1986 there were episodes of undervaluation from the first quarter of 1980 to the first quarter of 1984 and overvaluation from the second quarter of 1984 to the third quarter of 1986; thereafter the exchange rate was generally and marginally undervalued.
Keywords: Foreign exchange rates -- Ghana; Foreign exchange rates -- Nigeria; Economic development -- Ghana; Economic development -- Nigeria; Foreign exchange administration -- Ghana; Foreign exchange administration -- Nigeria; International relations